The Influence of Person-Job Fit on Organizational Commitment among Car Salesperson - Sesar, Agun; Bakar, Resekiani Mas; Rahmat, Abd. (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Organizational commitment refers to employees’ involvement, trust, and loyalty toward the organization, and it plays a key role in employee retention and improving company performance. This study aims to examine the influence of person-job fit—the compatibility between an individual and their job—on organizational commitment among car salespersons. Using a quantitative method with simple regression linear analysis and accidental sampling, data were collected from 140 respondents through the person-job fit scale translated by Astuti and Amir (2023) from Lauver and Kristof-Brown (2001), and the organizational commitment scale by Mowday, Porter, and Steers (1979), adapted by Rahmat, Bakar, and Anwar (2022). The results of simple linear regression show that person-job fit has a positive and significant effect on organizational commitment (R² = 0.138; β = 0.371; F = 22.026; p 0.001), indicating that the higher the person-job fit, the stronger the organizational commitment among salespersons. These findings suggest that companies should emphasize the recruitment process to enhance person-job fit, thereby increasing employee loyalty and productivity.